Comparative Analysis of Phytochemical Composition of Aqueous Extracts from Azadirachta indica and Vernonia amygdalina - Erhabor, Aisosa Prince; Erhabor, Osayawe Pride (Sciences of Phytochemistry, 2024)
Azadirachta indica (neem) and Vernonia amygdalina (bitter leaf) are among the most promising medicinal plants, valued for their broad spectrum of biological activities, including antibacterial, antifungal, anti-inflammatory, antiviral, antidiabetic, and antitumor properties. These plants play a central role in traditional Nigerian medicine for treating tropical diseases such as malaria, typhoid fever, yellow fever, and scabies. This study employed gravimetric analysis to identify and quantify the phytochemical compounds in both plants. Fresh leaves were collected, cleaned, air-dried, and their aqueous extracts were screened for key phytochemical constituents. The analysis revealed the presence of alkaloids, flavonoids, terpenoids, saponins, tannins, glycosides, and phenolic compounds in both extracts. Quantitative results showed that A. indica had the highest flavonoid content (13.80%), slightly surpassing V. amygdalina (13.62%). Similarly, terpenoids (13.13%) and alkaloids (10.67%) were more abundant in the neem extract compared to the bitter leaf (8.21% and 9.68%, respectively). Lower percentages of glycosides and saponins were observed, with neem containing higher concentrations of both compounds than the bitter leaf. These findings suggest that both plants are rich sources of bioactive compounds with potential applications in developing antibacterial and antifungal treatments. Further research into the phytochemical properties of these plants may facilitate the discovery of novel drugs to combat tropical diseases while reducing the reliance on synthetic chemicals, thus mitigating environmental degradation.